The male-female earnings gap for nurses in Germany: A pooled cross-sectional study of the years 2006 and 2012. (January 2019) - Muench, Ulrike; Dietrich, Hans
Abstract: Background: Nursing is one of the largest occupations for women in every country. Evidence suggests a substantial male-female pay gap for registered nurses in the U.S., possibly contributing to disparities between genders more broadly. Differences in motivation and skills between men and women have long been considered important factors in the gender earnings gap, but these factors are difficult to measure. Because of country specific educational pathways and limited upward job mobility in Germany, nurses tend to be more homogenous in their motivation to work and their work skills compared to the U.S. Objective: To study male-female earnings in the nursing labor market in Germany. Design: This is a pooled cross-sectional study of survey data collected for the years 2006 and 2012. Methods: We used a representative survey of nurses (n = 828) who are active labor force participants. In a multivariate ordinary least squares regression, the analysis estimated the log of monthly earnings for male and female nurses. The full model accounted for demographic, human capital, and geographic characteristics, in addition to employment characteristics, such as hours worked, additional education obtained, years of nursing experience, years of labor market experience, career inactivity, years with the employer, and responsibilities at work, among other factors. We conducted follow-up analyses to test alternative explanations for the pay gap, examining earnings for nurses who no longer worked in nursing and testing potential differences in motivation with the likelihood of working nightshifts and length of time with current employer. Results: Unadjusted monthly earnings for full-time male nurses were 30% higher, or 700 Euros more, than monthly earnings for full-time female nurses. In the fully adjusted analysis, male nurses out-earned female nurses by approximately 9.3%, or 260 Euros per month. Follow-up analyses suggested that better outside options exist for male than female nurses in the German labor market, while we found no support for gender differences in motivation.